2000
DOI: 10.1093/humrep/15.11.2333
|View full text |Cite
|
Sign up to set email alerts
|

Dose-finding study of triptorelin acetate for prevention of a premature LH surge in IVF: a prospective, randomized, double-blind, placebo-controlled study

Abstract: Gonadotrophin-releasing hormone agonists (GnRHa) are routinely used in IVF programmes to prevent an unwanted LH surge and consequent ovulation. Despite its widespread use in IVF, a convincing dose recommendation for GnRHa in IVF does not exist. In our opinion, the lowest possible dose of GnRHa should be used. Thus, we performed a prospective, randomized, double-blind, placebo-controlled study to determine the minimal daily dose of triptorelin acetate needed to suppress a premature LH surge during IVF treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(40 citation statements)
references
References 29 publications
0
38
0
2
Order By: Relevance
“…Over the past 25 years, GnRH agonists have been used successfully to prevent a premature LH surge in IVF cycles (1,2). More recently, GnRH antagonists were introduced to simplify the protocols and reduce the cost of the IVF treatment, but it is still debatable whether they are equally effective as agonists regarding live birth rate (3).…”
mentioning
confidence: 99%
“…Over the past 25 years, GnRH agonists have been used successfully to prevent a premature LH surge in IVF cycles (1,2). More recently, GnRH antagonists were introduced to simplify the protocols and reduce the cost of the IVF treatment, but it is still debatable whether they are equally effective as agonists regarding live birth rate (3).…”
mentioning
confidence: 99%
“…Pellicer et al (1989) found that there was no difference between the two protocols regarding the dose of gonadotropins necessary to reach an optimal response, fertilization and cleavage rates. Three other studies performed by Pellicer et al (1989), Ron-El et al (1990) and Kondaveeti-Gordon et al (1996) reported that there was evidence of higher amounts of gonadotropins required in the luteal start (Janssens et al, 2000) In conclusion, the two timing of starting the agonist were sufficiently potent to produce pituitary suppression in a short period of time. Stimulation requirements as the number of gonadotropin vials and the days of stimulation required to reach the criteria of hCG administration were comparable in the two groups.…”
Section: Discussionmentioning
confidence: 58%
“…Such a benefit explained the marked improvement of IVF results associated with the introduction of its use. As shown by placebo-controlled studies on GnRH agonists, LH surges occur in 20% of IVF patients, leading to cancellation of the IVF cycles (Edwards et al, 1996;Janssens et al, 2000). There are three main protocols involving the administration of GnRH: short, ultrashort and long protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Hesitation to use a depot agonist was related to the concern that it might lead to pituitary oversuppression, which could cause a luteal phase defect because of the absence of pituitary luteinizing hormone (10, 11). However, the use of halfdose depot GnRH for the COH cycle has resulted in reasonable IVF outcomes in infertile women (8)(9). Therefore, we used half doses of the depot form of GnRH agonist to suppress the ovary.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-nine patients underwent the GnRH-antagonist protocol. Corifollitropin alfa was administered on the menstrual cycle day 3. programs before their integration into daily use and have resulted in reasonable outcomes (6)(7)(8)(9). Furthermore, the drug industry may force the use of these innovative options, making them more popular.…”
Section: Methodsmentioning
confidence: 99%